2018
DOI: 10.1016/j.bbrc.2017.11.102
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment with a C1B5 peptide of protein kinase Cγ and a low dose of gemcitabine strongly attenuated pancreatic cancer growth in mice through T cell activation

Abstract: Although gemcitabine is an effective chemotherapeutic for pancreatic cancer, severe side effects often accompany its use. Since we have discovered that locally administered C1B domain peptides effectively control tumor growth without any side effects, the efficacy of co-treatment with this peptide and a low dose of gemcitabine on the growth of pancreatic cancer was examined. Two- and three-dimensional cell culture studies clarified that a co-treatment with C1B5 peptide and gemcitabine significantly attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Interestingly, when the dipeptide Fmoc-Cys-Tyr-NH 2 was reacted with HATU, we found that the side product could be installed both on the phenol group of Tyr as also on the sulfhydryl group of Cys. Therefore, we tested these reaction conditions on the peptide C1B5 141–151 subdomain peptide (RCVRSVPSLCG) of protein kinase C (PKC) γ isozymes, which possess 2 cysteines (but no tyrosine or lysine or free N-terminus amine) and bears anticancer properties [ 157 ]. Again, a side product with two aminium moieties on the two cysteines was formed and characterized with ESIMS.…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, when the dipeptide Fmoc-Cys-Tyr-NH 2 was reacted with HATU, we found that the side product could be installed both on the phenol group of Tyr as also on the sulfhydryl group of Cys. Therefore, we tested these reaction conditions on the peptide C1B5 141–151 subdomain peptide (RCVRSVPSLCG) of protein kinase C (PKC) γ isozymes, which possess 2 cysteines (but no tyrosine or lysine or free N-terminus amine) and bears anticancer properties [ 157 ]. Again, a side product with two aminium moieties on the two cysteines was formed and characterized with ESIMS.…”
Section: Reviewmentioning
confidence: 99%
“…High blood neutrophil‐to‐lymphocyte ratios are associated with larger tumor size, less differentiated tumors, increased tumor vascularization, poor overall survival, and recurrence‐free survival rates in numerous cancers . However, other studies link neutrophil markers to better survival rates . Rather than their sheer number, the types of tumor‐infiltrating neutrophils and their state of differentiation/activation, as we will describe here, may play a significant role in cancer.…”
Section: Introductionmentioning
confidence: 86%
“…[9][10][11] However, other studies link neutrophil markers to better survival rates. [12][13][14][15][16][17] Rather than their sheer number, the types of tumor-infiltrating neutrophils and their state of differentiation/activation, as we will describe here, may play a significant role in cancer. Their ability to leave the bone marrow as Abbreviations: ABX, antibiotics; ARG1, arginase 1; BMN, bone marrow neutrophil; DAMP, damage-associated molecular patterns; DSS, dextran sulfate sodium; FLT3L, FMS-like tyrosine kinase 3 ligand; fMLF, formyl Met-Leu-Phe; FPR, formyl Met-Leu-Phe receptor; FXR, farnesoid X receptor; GF, germfree; GFI-1, growth factor independent 1; gMDSC, granulocytic myeloid-derived suppressor cell; HDN, high-density neutrophil; HGF, hepatocyte growth factor; HIF, hypoxia-inducible Factor; ILC3, type 3 innate lymphoid cell; LDN, low-density neutrophil; LOX-1, lectin-like oxidized low-density lipoprotein receptor-1; MAMP, microbial-associated molecular patterns; MDSC, myeloid-derived suppressor cell; MMP, matrix metalloproteinase; MPO, myeloperoxidase; NET, neutrophil extracellular trap; NOD1, nucleotide-binding oligomerization domain-containing protein 1; PBN, peripheral blood neutrophil; PRR, pattern recognition receptor; RNS, reactive nitrogen species; ROS, reactive oxygen species; SCF, stem cell factor/ c-kit ligand; SCFA, short-chain fatty acid; SFB, segmented filamentous bacteria; SPF, specific-pathogen-free; TAN, tumor-associated neutrophil; TBI, total body irradiation; TCM, tumor-conditioned medium; VEGF, vascular endothelial growth factor a functional and mature, or attenuated and immature granulocyte can be heavily influenced by the microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Clinical Trials target the tumor microenvironment of PDAC ( Tomás-Bort et al, 2020 ). 3D cell cultures, and specially PSC/PDAC spheroids, are important tools for screening of cancer and stroma targeting drugs permitting a validation step preceding animal testing and reduce the number of animals required ( Ishiguro et al, 2018 ). 3D modeling of cell culture may aid in drug discovery and biological treatment.…”
Section: In Vitro Preclinical Modelsmentioning
confidence: 99%